Faktor Kesulitan Berbahasa Indonesia pada Mahasiswa Universitas Muhammadiyah Yogyakarta Penutur Arab Asal Yaman - Muhammad Arifin Ilham; Putri Hilman, Yuke Pitaloka; Nurmala, Mia; Syihabuddin, Syihabuddin (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2025)
This research aims to identify factors of language difficulties among Arabic-speaking students at Muhammadiyah University of Yogyakarta from Yemen in learning Indonesian. The research method used is qualitative research with interviews as the data collection technique. The process involves open-ended questions that allow respondents to explain their views in detail, while the researcher takes notes, analyzing the data collected. The results of this research are that there are two factors of difficulty in speaking Indonesian among Arabic speakers from Yemen, students at Muhammadiyah University of Yogyakarta, namely internal factors such as feeling foreign to Indonesian, significant differences in structure and vocabulary with Arabic, and a lack of guidance in the learning process. And the second is external factors such as the use of regional languages ​​by the surrounding environment which makes understanding and communication difficult.